Problems of Arabic - Indonesian Text Translation for Beginner Students at the Center for Foreign Language Studies (PSBA) - Ulfah, Yeniati; Zainullah, Ahmad; Yusuf, Afnan (Insya : Journal of Arabic Studies, 2024)
This research aims to reveal the problems faced by novice students as novice translators in translating Arabic-Indonesian texts. This study used descriptive qualitative method. The subjects of the research were students of the D2 class Arabic language program at the Center for Foreign Language Studies (PSBA). The process of collecting and analyzing data through observation, tests and interviews. The results of this research show that there are two factors in translating Arabic texts, namely linguistic and non-linguistic factors. In terms of linguistic factors, the data shows that 13 students experienced problems in mastering vocabulary, 4 students in nahwu and 9 students in using equivalent words. Meanwhile, non-linguistic factors are related to motivation to learn Arabic. In the data presented, there were 4 students who lacked motivation and interest in Arabic.